Effectiveness of Pop Music in Improving High School Students’ English Pronunciation - Muhammad Fariz Yanuar Ramadhan; Hartatya Novika; Nurhasanah Nurhasanah; Harum Mustika (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
This study investigates the effectiveness of pop music as a pedagogical tool to enhance English pronunciation in high school students. This research focused on a single group of participants with a sample size of 15 who underwent both pretest and posttest assessments. The results of both the pretest and the posttest, which measured the students' improvements in pronunciation accuracy, were then meticulously calculated and analysed using SPSS (Statistical Package for the Social Sciences). The results indicated a statistically significant improvement in the pronunciation skills of the students from pretest to posttest. Students who engaged with pop music reported higher levels of motivation to improve their English pronunciation skills. The research revealed that students became more active participants in the learning process, displaying heightened motivation and interest in learning English. Thus, the findings indicate that pop music not only improves pronunciation but also contributes to a more enthusiastic and interactive classroom atmosphere.